2020
DOI: 10.1088/1361-648x/aba777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bond on negative thermal expansion of Prussian blue analogues MCo(CN)6 (M = Fe, Ti and Sc): a first-principles study

Abstract: Negative thermal expansion (NTE) is an abnormal physical behavior that has promising applications for high precision thermal control. Since Prussian blue analogues have the two central linking atoms of -C≡N-, they have large structure exibility and are suitable to explore new NTE materials. However, understanding the nature of structure exibility from the point of view of chemical bonding is important and urgent. Here, we adopt for the rst time rst-principles calculations to predict that the cubic TiCo(CN) 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
3
19
0
Order By: Relevance
“…The thermal expansion difference of the Ti–N bond is much larger than that of the Co–C bond, indicating that the NTE driving force of TiCo­(CN) 6 is mainly the transverse thermal vibrations of the Ti–N bonds. These results were also consistent with the previous report; i.e., the total charge density in the (001) plane of TiCo­(CN) 6 shows that the Co–C bonds are weak covalent, while the Ti–N bonds display a strong electrovalent bonding nature. With H 2 O molecule insertion, the “apparent” thermal expansion of the Ti–N bond is switched to the PTE behavior in TiCo­(CN) 6 ·2H 2 O, while thermal expansion of the Co–C bonds displays the same behavior as that of TiCo­(CN) 6 , suggesting that the H 2 O molecules have an effect mainly on the chemical bond of Ti–N.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The thermal expansion difference of the Ti–N bond is much larger than that of the Co–C bond, indicating that the NTE driving force of TiCo­(CN) 6 is mainly the transverse thermal vibrations of the Ti–N bonds. These results were also consistent with the previous report; i.e., the total charge density in the (001) plane of TiCo­(CN) 6 shows that the Co–C bonds are weak covalent, while the Ti–N bonds display a strong electrovalent bonding nature. With H 2 O molecule insertion, the “apparent” thermal expansion of the Ti–N bond is switched to the PTE behavior in TiCo­(CN) 6 ·2H 2 O, while thermal expansion of the Co–C bonds displays the same behavior as that of TiCo­(CN) 6 , suggesting that the H 2 O molecules have an effect mainly on the chemical bond of Ti–N.…”
supporting
confidence: 93%
“…30 i.e., the total charge density in the (001) plane of TiCo(CN) 6 shows that the Co−C bonds are weak covalent, while the Ti−N bonds display a strong electrovalent bonding nature. With H 2 O molecule insertion, the "apparent" thermal expansion of the Ti−N bond is switched to the PTE behavior in TiCo(CN) 6 • 2H 2 O, while thermal expansion of the Co−C bonds displays the same behavior as that of TiCo(CN) 6 , suggesting that the…”
mentioning
confidence: 99%
“…This is interesting in its own right, as transverse low-energy phonons—such as tilts—typically underlie negative thermal expansion. 72–74…”
Section: Resultsmentioning
confidence: 99%
“…84,85 Yet, there are no confirmed cases of such distortions and a computational study found these modes, particularly the unconventional tilt, to be more energetically unfavourable compared to conventional tilts. 72 This is presumably due to the strong preference for a linear M′–C–N arrangement, as discussed above, whereas the unconventional distortions require nonlinear binding at both ends of the linker. 86 While this simplifies the study of distortions in PBAs, as only conventional modes need to be considered, it also limits the diversity of possible distortions.…”
Section: Discussionmentioning
confidence: 98%
“…Detailed discussion of the QHA can be found in the references (Kuzkin and Krivtsov, 2015). In our previous work, the QHA provided a reasonable description of the dynamic properties of the compound (Liu et al, 2015;Chang et al, 2018;Li et al, 2020).…”
Section: Computation Methodsmentioning
confidence: 97%